2021
DOI: 10.3390/app11209536
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Powders Containing Sb, Ni, and O for the Design of a Novel CO and C3H8 Sensor

Abstract: In this work, powders of NiSb2O6 were synthesized using a simple and economical microwave-assisted wet chemistry method, and calcined at 700, 800, and 900 °C. It was identified through X-ray diffraction that the oxide is a nanomaterial with a trirutile-type structure and space group P42/mnm (136). UV–Vis spectroscopy measurements showed that the bandgap values were at ~3.10, ~3.14, and ~3.23 eV at 700, 800, and 900 °C, respectively. Using scanning electron microscopy (SEM), irregularly shaped polyhedral micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…In reference [13], the band gap was reported as 3.92 eV. Another study [29] reported values in the range of 2.6-2.8 eV for a material calcined at 700 • C and 2.8-2.9 eV for a material calcined at 900 • C. It should be noted that the forbidden band value is strongly influenced by the synthesis method and the heat treatment employed, as mentioned by several authors [13,22,29], which is consistent with the findings of this study.…”
Section: Uv-vis Analysismentioning
confidence: 94%
See 2 more Smart Citations
“…In reference [13], the band gap was reported as 3.92 eV. Another study [29] reported values in the range of 2.6-2.8 eV for a material calcined at 700 • C and 2.8-2.9 eV for a material calcined at 900 • C. It should be noted that the forbidden band value is strongly influenced by the synthesis method and the heat treatment employed, as mentioned by several authors [13,22,29], which is consistent with the findings of this study.…”
Section: Uv-vis Analysismentioning
confidence: 94%
“…The nickel antimonate synthesis was conducted using a wet chemistry method reported in [ 22 , 23 ]. A stoichiometric 2:1 molar ratio of nickel nitrate hexahydrate and antimony trichloride was used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation